The Impact of the Digital Yuan on the Transmission Mechanism of Monetary Policy in China - Liang, Xiao; Klement, Josef, 1990-; Bednář, Milan, 1991-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2025)
This thesis examines how the Digital Yuan (e-CNY) affects the transmission of monetary policy in China by combining theoretical, qualitative, and empirical analysis. Its theoretical framework outlines China’s quantity-based and price-based policy tools and evaluates how digital currency features such as traceability and programmability reshape liquidity control and market autonomy. The qualitative analysis highlights both opportunities and risks: the Digital Yuan may weaken the effectiveness of the money multiplier while strengthening the central bank’s guidance of interest rates. The empirical study uses provincial quarterly panel data from 2015 to 2023 and constructs a fixed-effects model incorporating the Monetary Digitalisation Index (MDI). The results indicate that the Digital Yuan enhances price-based transmission mechanisms, has a limited but observable impact on quantity-based mechanisms, and exerts stronger transmission effects in eastern provinces with higher levels of financial development.
Vedoucí práce: Josef Klement
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses